Randomised, open-label, phase II study comparing the efficacy and the safety of cabazitaxel versus weekly paclitaxel given as neoadjuvant treatment in patients with operable triple-negative or luminal B/HER2-negative breast cancer (GENEVIEVE). (October 2017) - Kümmel, Sherko; Paepke, Stefan; Huober, Jens; Schem, Christian; Untch, Michael; Blohmer, Jens Uwe; Eiermann, Wolfgang; Gerber, Bernd; Hanusch, Claus; Hilfrich, Jörn; Jackisch, Christian; Schneeweiss, Andreas; et al.
Abstract: Background: The GENEVIEVE study compared the pathological complete response (pCR) rate (ypT0/is ypN0/+) in patients with operable human epidermal growth factor receptor 2 (HER2)–negative breast cancer (BC) treated with either cabazitaxel or paclitaxel. Methods: GENEVIEVE was a prospective, multicentre, randomised, open-label, phase II study comparing the efficacy and the safety of four 3-weekly cycles cabazitaxel versus 12 weeks of paclitaxel given as neoadjuvant treatment. Primary end-point was the pCR rate defined as the complete absence of invasive carcinoma on histological examination of the breast irrespective of lymph node involvement (ypT0/is, ypN0/+) after the taxane treatment. Patients could receive an anthracycline-based therapy thereafter. Results: Overall, 333 patients were randomised and started treatment with 74.7% and 83.2% of patients completing treatment in the cabazitaxel and paclitaxel arms, respectively. Patients in cabazitaxel arm had a significantly lower pCR rate compared to the paclitaxel arm (1.2% versus 10.8%; p = 0.001). A total of 42 (25.3%) patients in the cabazitaxel arm and 17 (10.2%) in the paclitaxel arm had at least one serious adverse event (p < 0.001). Dose reductions were observed in 9.6% patients in the cabazitaxel arm compared to 11.4% in the paclitaxel arm (p = 0.721). Main reason for dose reductions was non-haematological toxicities in 3.0% versus 7.8% (p = 0.087), respectively. Conclusions: The GENEVIEVE study showed no short-term effect of cabazitaxel in triple-negative or luminal B/HER2-negative primary BC, while there seemed to be no differences in drug exposure and patient compliance between the two arms. Clinical trials registration: ClinicalTrials.govNCT01779479 . Highlights: No short-term effect of cabazitaxel was detected compared to paclitaxel as neoadjuvant treatment for breast cancer. No differences in drug exposure and patient compliance were observed between the two arms. The rate of haematological toxicities was significantly higher in patients receiving cabazitaxel compared to paclitaxel.